Entecavir as treatment for reactivation of hepatitis B in immunosuppressed patients - Brost, Sylvia; Schnitzler, Paul; Stremmel, Wolfgang; Eisenbach, Christoph (World journal of gastroenterology, 2010)
Entecavir as treatment for reactivation of hepatitis B in immunosuppressed patients
Gesehen am 01.03.2023